Insights into the Roles of Desolvation and π‐Electron Interactions during DNA Polymerization. Issue 4 (12th February 2013) - Motea, Edward A.; Lee, Irene; Berdis, Anthony J.
Abstract This report describes the use of several isosteric non‐natural nucleotides as probes to evaluate the roles of nucleobase shape, size, solvation energies, and π‐electron interactions as forces influencing key kinetic steps of the DNA polymerization cycle. Results are provided using representative high‐ and low‐fidelity DNA polymerases. Results generated with the E. coli Klenow fragment reveal that this high‐fidelity polymerase utilizes hydrophobic nucleotide analogues with higher catalytic efficiencies compared to hydrophilic analogues. These data support a major role for nucleobase desolvation during nucleotide selection and insertion. In contrast, the low‐fidelity HIV‐1 reverse transcriptase discriminates against hydrophobic analogues and only tolerates non‐natural nucleotides that are capable of hydrogen‐bonding or π‐stacking interactions. Surprisingly, hydrophobic analogues that function as efficient substrates for the E. coli Klenow fragment behave as noncompetitive or uncompetitive inhibitors against HIV‐1 reverse transcriptase. In these cases, the mode of inhibition depends upon the absence or presence of a templating nucleobase. Molecular modeling studies suggest that these analogues bind to the active site of reverse transcriptase as well as to a nearby hydrophobic binding pocket. Collectively, the studies using these non‐natural nucleotides reveal important mechanistic differences between representative high‐ and low‐fidelity DNA polymerases during nucleotide selection and incorporation.